A fully-resolved immersed boundary numerical method to simulate particle-laden viscoelastic flows - Fernandes, C. (2019)
[extract] Fluid-particle transport systems present a significant practical relevance, in several engineering applications, such as oil sands mining and polymer processing. In several cases it is essential to consider that the fluid, in which the particles are dispersed, has underlying viscoelastic characteristics.